RUTA TURÍSTICA CULTURAL DEL CANTÓN PINDAL DE LA PROVINCIA DE LOJA - Sanchez Ruiz, Juan Jefferson (2016)
Ecuador a country with vast natural and cultural wealth. The diversity of its four regions has resulted in hundreds of thousands of species of flora and fauna. Ecuador is considered one of the 17 countries where the greatest biodiversity is concentrated, and is also the largest country in the world biodiversity km2. Most of its flora and fauna live in 26 protected areas by the State. It also has historical and cultural attractions that make a country worthy of visit. La province of Loja is no exception featuring cultural and natural attractions is a province with a rich culture that is undertaking projects to increase the influx of tourists to its various cantons. Pindal one of sixteen districts of the province of Loja with a great diversity of natural and cultural attractions. From the point of view Pindal Cantons has a great cultural and natural wealth was important to develop work investigation. For which targets were raised, among them the general objective; "Designing the cultural tourist route Pindal Canton of the Province of Loja" .- this objective covers all matters concerning the entire development of research work, to achieve the same three specific objectives were raised; Make the tourist diagnosis of the current situation of the Canton Pindal; to fulfill the first objective techniques are used, such as direct observation, interview, Matrix tourist diagnosis of Ricaurte Carla communities Quijano, Tourist inventory sheets (MINTUR) of Ecuador, Sheets nesting attractions of the Ministry of Tourism and as instruments and materials quaking support information Land Use Plan was also used were the complement to collect political, social, economic information. Geographic and tour the Canton and finally the SWOT matrix was used to determine the current status of the Canton Pindal; second objective; Propose the design of the tourist cultural route Pindal Canton; o fulfill the first objective techniques are used, such as direct observation, interview, Matrix tourist diagnosis of Ricaurte Carla communities Quijano, Tourist inventory sheets (MINTUR) of Ecuador, Sheets nesting attractions of the Ministry of Tourism and as instruments and materials quaking support information Land Use Plan was also used were the complement to collect political, social, economic information. Geographic and tour the Canton and finally the SWOT matrix was used to determine the current status of the Canton Pindal; second objective; He proposed the design of the tourist cultural route Pindal Canton; instruments like a georeferencing system (GPS) was used to make the lifting of coordinates, altitude, travel time and distances; Digital camera support and a matrix developed by the Ministry of Tourism of Ecuador to validate routes, the same components needed were established for the development of the Cultural Tourist Route Pindal using pictograms Canton Natural and Cultural attractions tourism and support service activities, and the brand was designed to identify the most relevant canton and then the name of the route called "Route Tourism Cultural Maize and Waterfalls", all this was finally presented in the design of a cuadriptico raised . A script and itinerary of the 5 route, following the order established in the same was also developed; Third Objective.-Socialize the proposal from the tourist cultural route of the Canton Pindal to those involved in tourism. To meet this objective MARPP technique comprising three phases for development was used. The first phase by the Mayor Livar trade Bustamante Celi was presented to ask date for the socialization of the proposal for further response to the call to all those involved in tourism; the second phase, the results of research on the development of the so-called Cultural Tourist Route Corn was presented and waterfalls; and the third phase the conclusions and recommendations proposed by the attendees indicated. As a result of socialization it is determined that the Cultural Tourism Route "Maize and Waterfalls" furnish a better way to tourism development in the canton since it has taken into account the main relevant the same natural and cultural attractions . Finally, conclusions and recommendations of the thesis which are directed in full to the Autonomous Government Decentralized Canton Pindal for execution of the socialized and to present in a better way the benefits of the canton proposal and the respective opening Give raised the realization of projects aimed at tourism. It has been a limiting factor for lack of information and limited access to the attractions of private property.